VANET routing protocol for V2V implementation: A suitable solution for developing countries. Issue 1 (1st January 2017) - Yasser, Ahmed; Zorkany, M.; Abdel Kader, Neamat
Abstract: During the last decade Intelligent Transportation System (ITS) research and development, including its implementation in a real life going through the optimization in order to have the best and accurate results is growing exponentially. Now ITS topics are standing on a solid ground. Many European countries and USA started to implement and use them. In the developing countries the infrastructure is not established well with a lot of challenges (ex. Infrastructure cost, …). In this paper, Vehicle-to-Vehicle (V2V) implementation will be used as a standalone for ITS architecture in the developing countries without Road site units (RSU) infrastructure to overcome the current challenges. To do that, a full simulation for different Vehicular Ad-Hoc Network (VANET) routing protocols will be done using Opnet simulator to select the best protocol for V2V Implementation. Then the best V2V routing protocol based on the paper's Key Performance Indicators and point of view will be used to compare between two different architectures, one with V2V + RSU implementation and the other one with proposed V2V only implementation. The results demonstrate that the proposed ITS architecture based on V2V only without RSU is capable of implementing ITS in developing countries.